Evaluation of urea loaded nano clay biopolymer composites and nitrification inhibitors on nitrogen use efficiency under maize-wheat cropping system - Premlata Meena; K. M. Manjaiah; Kapil Atmaram Chobhe; Vinod Kumar Sharma; Hanuman Singh Jatav; Mamta; Ajit Kumar Meena (Discover Applied Sciences)
Abstract Across the globe, cereal crops have only < 30% nitrogen (N) use efficiency (NUE) due to significant loss of N.During previous decade nitrification inhibitors (NI) were promoted for better N management and utilization. However, recentresearch had been focused on developing nanoclay polymer composite based (NCPC)slow-release fertilizer for better nutrient delivery and efficient use.This study aims to synthesize a novel nano clay biopolymer composite (NCBPC) product to replace conventional fertilizers to enhance NUE. Nanoclay biopolymer composite was synthesized using different polymers such as acrylic acid and maize flour as a starch source at a 20% replacement level with acrylamide monomers via free radical polymerization and N,N,-methylene bisacrylamide as crosslinkers, nano-bentonite as diffusion barrier and ammonium persulfate as initiator. The concentration of nitrification inhibitors (DCD and 4-Fluoro-3-nitrobenzaldehyde, Schiff bases) was 1% and 3% of the N dose. Fourier transform infrared (FTIR) spectra, X-ray diffraction (XRD) and scanning electron microscope (SEM) were employed for characterization of NCBPCs and a laboratory incubation study conducted to monitor N release pattern. Field evaluation of prepared product carried out in randomized complete block design (RCBD) with three replications in maize and wheat crops. The recommended amount of N was 150 kg ha−1and applied at the rates of 0, 50, 75, and 100% by using urea and NCBPC (loaded with urea and nitrification inhibitors) in the three equal split doses at 45, 60, and 90 DAS (days after sowing). Our results highlightthat, NCBPC loaded with 75%N + NI maintains higher ammoniacal N and lower nitrate N in soil leaching studies and promotes better or comparable leaf chlorophyll content, root growth (length, volume and surface area), grain and straw yield as obtained under 100% N through conventional prilled urea fertilization in both the crops. NCBPC loaded with 75% N and 3% dicyandiamide (DCD) (T3) emerged as the best combination inboth the crops. It had greater apparent N recovery (40.43% and 40.60%) and agronomic NUE (36.20% and 37.10%) than conventional fertilizer in both crops, respectively. Therefore, combined application of NCBPC loaded with urea and NIs offer 25% cutdown of total N requirement and same time may be focused for better yield and N use efficiency in maize and wheat crops.